Life history parameters of Tetranychus cinnabarinus (Acari: Tetranychidae) on leaves of carnation, Dianthus caryophyllus - TELLO-M., VÍCTOR; VARGAS-M, ROBINSON; ARAYA-C., JAIME (Revista Colombiana de Entomología, 2009)
The biology of Tetranychus cinnabarinus on Dianthus caryophyllus var. Celta was studied under controlled conditions of 29.44 ± 1.47°C temperature, 42.35±5.01% RH and 14:10 h (L:D) photophase. The cycle from egg to adult lasted 12.84 ± 0.21 days, with 80.22% survival. The sex ratio was 76.28% females: 23.72% males. The mean female longevity was 24.28 ± 1.37 days and the mean daily oviposition rate was 3.92 ± 0.21 eggs/female/day. The intrinsic rate of increase (rm) was 0.183; the finite rate of increase () was 1.201 individuals/female/day; the mean generation time (T) was 20.24 days; and the net rate of reproduction (R0) was 40.809. The development patterns of T. cinnabarinus fall within those described for mites of the family Tetranychidae.